Analysing EU Treaty-Making and Litigation With Network Analysis and Natural Language Processing - Ovádek, Michal; Dyevre, Arthur; Wigard, Kyra (Frontiers in Physics, 2021)
We apply network analysis and topic modeling techniques to explore the evolution of the European Union's treaty making activity and the patterns of litigation they have given rise to. Our analysis reveals that, despite the expansion of the bloc's policy remit, its treaty-making activity retains a strong economic focus. Among the many agreements negotiated by EU institutions, the European Economic Agreement, the Ankara Agreement with Turkey and the World Trade Organization Agreement form the largest clusters of litigated cases. EU international agreements are disproportionately litigated in cases pertaining to residence rights and competition law.